2020
DOI: 10.2147/idr.s223243
|View full text |Cite
|
Sign up to set email alerts
|

<p>Risk Factors for Carbapenem-Resistant <em>Klebsiella pneumoniae</em> Bloodstream Infections and Outcomes</p>

Abstract: The incidence of carbapenem-resistant Klebsiella pneumoniae (CRKP) bloodstream infections (BSIs) is increasing globally; however, little has been reported on the risk factors and outcomes of CRKP BSIs in central China. This study aimed to determine the clinical risk factors for CRKP BSIs and the outcomes of CRKP BSIs. Patients and Methods: We performed a case-control study of 239 patients with K. pneumoniae BSIs who were treated at Henan Provincial People's Hospital between July 2017 and July 2018. The cases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…In addition, it could be further optimized in the initial design of the study grouping, replacing the survivors/non-survivors with the treatment success/treatment failure. The corresponding groupings were well defined in the study of Youhua Yuan et al 25 …”
Section: Discussionmentioning
confidence: 78%
“…In addition, it could be further optimized in the initial design of the study grouping, replacing the survivors/non-survivors with the treatment success/treatment failure. The corresponding groupings were well defined in the study of Youhua Yuan et al 25 …”
Section: Discussionmentioning
confidence: 78%
“…Horikoshi et al showed a positive correlation between days on carbapenems and carbapenems resistance in the pediatric population (Horikoshi et al, 2017). Another case–control study involving Klebsiella pneumoniae bloodstream infection found that carbapenem use caused 9.98-fold increase in the odds of acquiring carbapenem resistance (Yuan et al, 2020). Carbapenem exposure within 1 month before the onset of bloodstream infection was found by other authors to be the only risk factor for developing CRK infection (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been noted in a study where diabetes was associated in 30.6% of patients and was not a significant associated risk factors for CRKP (p value = 0.89) whereas invasive procedure as catheter was proved to be associated with CRKP (p value was 0.001). 15 Assessing resistance to ertapenem, it was a sensitive screening test for detecting carbapenem resistance. 12 Nevertheless, resistance to this carbapenem is not a direct indicator for the production of carbapenemases.…”
Section: Discussionmentioning
confidence: 99%